8x+6+7x-3=

Simple and best practice solution for 8x+6+7x-3= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x+6+7x-3= equation:


Simplifying
8x + 6 + 7x + -3 = 0

Reorder the terms:
6 + -3 + 8x + 7x = 0

Combine like terms: 6 + -3 = 3
3 + 8x + 7x = 0

Combine like terms: 8x + 7x = 15x
3 + 15x = 0

Solving
3 + 15x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 15x = 0 + -3

Combine like terms: 3 + -3 = 0
0 + 15x = 0 + -3
15x = 0 + -3

Combine like terms: 0 + -3 = -3
15x = -3

Divide each side by '15'.
x = -0.2

Simplifying
x = -0.2

See similar equations:

| 2x+x+x+50+x+20=360 | | 2*11-3y=16 | | x-7.48=3.8 | | 21z^2+13z-20= | | (4+u)(2u-7)=0 | | 75x^3+100x^2-27x-36=0 | | 6t-11=3t-5 | | 7x^3+100x^2-27x-36=0 | | 2tan^2x+1=7 | | Log(x+4)=log(4x-5) | | 2*14-3y=16 | | 10=2(6n-1) | | 2930=c+100+200 | | solve-4p+3q=-6 | | 5(2x+8)-(3x+1)+9x= | | 4n+7-6n=5-4n+4 | | y=(200+.90(y-230))+100+200 | | 2*17-3y=16 | | -7=y+1 | | 16y^2-10y-21= | | 169-24x+x^2=x^2 | | 7y+3(y-4)=5(y+1)-4 | | (-12x-9)+(24x+4)=43 | | (2x-3y)+8(x+y)-(4y+2x)= | | 8x-29=3(x-8) | | 0.5(5)-7(0.5)=8-(4x+6) | | cos(x+5)= | | -87+71= | | 5*-1-y=11 | | 11=-19+b | | 36x+48x^2+7x^3= | | 7-(-65)= |

Equations solver categories